The King : the life of Charles III - Andersen, Christopher P. (Gallery Books, 2022)
"Since the day Charles Philip Arthur George was born, he has been groomed to be King. After more than seventy years of waiting, he finally ascends the throne. The King examines the private life of this historically important and controversial figure, set against the grand, thousand-year sweep of the British monarchy. This richly detailed biography covers it all, from his military training to his marriage to Lady Diana, through their separation and her tragic death to his marriage to Camilla Parker Bowles. In the process, it provides a balanced but fully honest look into the life of the new monarch"--